ANALYSIS OF THE EFFECT OF BIOFERTILIZER AGENT ACTIVITY ON SOIL ELECROLIT CONDUCTIVITY & ACIDITY IN REAL TIME WITH THE SMART BIOSOILDAM METHOD - Widiasmadi, Nugroho (IJRDO - Journal of Mechanical And Civil Engineering, 2020)
The objective of this analysis improvement of soil infiltration rate on Grumosol agroland with involve biofertilizer MA-11 on the Biosoildam . As a control is original soil without microbial activity triggered.The research was carried out on January to Juni 2020 at area of shallot agroland in Blora Districts. The research was use double ring infiltrometer to measure soil infiltration with three replication on each distance from Biohole and use electrolit conductivity meter (EC) to measure soil fertility by salt ion consentration and soil acidity. The measurement was done in every five minute and observtian periode every fifteen days along forty five days. The result of research show that the highest of infiltration rate, infiltration capacity , fertility & acidity was happened on soil with involve Biofertilizer MA-11.The infiltration rate shows a constant value at a level of 40 to 90 cm / hour which is achieved after the 30th day. Meanwhile, the EC value in stable conditions is achieved on the 35th day with a value between 650 - 700 uS / cm. So that the activity of biological agents on gromosol soils with an optimal infiltration rate on the 33rd day.